Estudo fitoquímico de plantas do Nordeste: Annona squamosa. obtenção de derivados reacionais do ácido caurenóico - Crisafulli, Rudy (2007)
Annona squamosa is a common tree popularly know as “ata”. In the folk medicine is used for treatment of stomach diseases, headache, diarrhea and for removal of louse. Phytochemical investigation of EtOH and hexanic extraction using chromatographic techniques allowed identification of kaurenoic acid an 16, 17-Dihidroxy-ent-kauran-19-oic acid. Derivative of kaurenoic acid were obtained in order to obtain biological activity and structure elucidation. The hexanic extract of trunk was submmited to hydrolise with KOH/MeOH, followes by methylation to yield ester misture identified by CG-MS as: tetradecanoic acid, penthadecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecadi-9,11-en-oic acid, octadecadi-9,12-en-oic acid, octadec-9-enoic acid, octadecanoic acid. All natural compounds and derivatives were characterized by spectroscopic analysis including NMR 1H and 13C, IV and MS. Compounds structures were confirmed by comparison with literature data.